P-Wave Duration and Dispersion in Patients With Emery-Dreifuss Muscular Dystrophy. (1st October 2011) - Russo, Vincenzo; Rago, Anna; Palladino, Alberto; Papa, Andrea Antonio; Di Meo, Federica; Della Cioppa, Nadia; Golino, Paolo; Russo, Maria Giovanna; Calabrò, Raffaele; Politano, Luisa; Nigro, Gerardo
Abstract : Background: Paroxysmal episodes of atrial fibrillation frequently occur in Emery-Dreifuss muscular dystrophy (EDMD). Although previous studies have documented a variety of electrocardiographic abnormalities in EDMD, little is still known about P-wave dispersion (PD), an independent risk factor for the development of atrial fibrillation. The aim of our study was to evaluate the P-wave duration and PD in patients with EDMD with conserved systolic and diastolic cardiac function. Methods: The study involved 36 patients with EDMD (age, 20 [SD, 12] years; 26 men) and 36 healthy subjects used as controls, matched for age and sex. P-wave dispersion was carefully measured using 12-lead electrocardiogram. Compared with the healthy control group, patients with EDMD presented increased maximum P-wave duration (108.2 [SD, 22.2] vs 97.8 [SD, 11] milliseconds, P = 0.04) and PD (51.4 [SD, 12.8] vs 39.3 [SD, 9.7] milliseconds, P = 0.004) values. No statistically significant differences in left atrium diameter (37.1 [SD, 2.9] vs 34.1 [SD, 4.2] mm, P = 0.3) and maximum left atrium volume (15.2 [SD, 3.8] vs 14.1 [SD, 4.2] mL/m 2, P = 0.4) were found between the 2 groups. We divided our study population into 2 subgroups, according to the different genetic diagnosis, patients with laminopathy EDMD (n = 17) or with emerinopathy EDMD (n = 19). No statistically significant differences were found in PD between the 2 subgroups (54.6 [SD, 15.6] vs 50.2 [SD, 11.5] milliseconds, P = 0.4). Conclusions: Our study showed a significant increase of maximum P-wave duration and PD in patients with EDMD with conserved systolic and diastolic cardiac function.